Distributed Execution of Scenario-based Specifications of Structurally Dynamic Cyber-Physical Systems. (2016) - Greenyer, Joel; Gritzner, Daniel; Katz, Guy; Marron, Assaf; Glade, Nils; Gutjahr, Timo; König, Florian
Abstract: Cyber-physical systems are found in many areas, e.g., manufacturing or smart cities. They consist of multiple components that cooperate to provide the desired functionality. This need for cooperation causes complex interactions between components, which makes developing cyber-physical systems difficult, especially systems whose component structure changes dynamically at runtime. We have created a formal, scenario-based specification method which makes it easier to develop distributed cyber-physical systems. We previously presented an approach for the distributed execution of such specifications based on naive and inefficient broadcasting. In this paper we propose a more efficient approach which uses the available network resources more economically.